Contestation on Religious Interpretation in Contemporary Aceh Sharīa: Public Caning in Prison as the Case of Study - Husni Mubarrak; Faisal Yahya; Iskandar Iskandar (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aimed to discuss the debate and controversy surrounding interpretations that are considered authoritative about interpreting Sharīa proposition regarding the ta'zīr public caning legal procession in prisons in Aceh, from what was previously held in an open space. The debate occurred and took place in various media, including social media, following the issuance of the 2018 Aceh Governor's Regulation concerning the relocation of the punishment procession. The discussion continued long enough to debate the interpretation which is considered the most valid regarding the necessity of caning for being witnessed by a group of believers (mukmin); the selection of the place where the punishment will be carried out; until the legal reasoning, intent and purpose of the caning punishment itself to be witnessed in public space according to Sharīa, as explicitly stated and interpreted in the Al-Qur’an Surah An-Nur: verse 2. By using literature studies and empirical investigations as the method, this article would like to use synthesis approach for analysis by putting theory “authoritative” and “authoritarianism” as the framework. The research finding shows that certain view which has been popularized through media is supposed as an authoritative interpretation and understood as the “should be” according to sharīa by the public, so that must be imposed of caning and openly witnessed (not in jail) during the formalization of Islamic law in contemporary Aceh.